If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 4 + h = 23 Combine like terms: -5 + 4 = -1 -1 + h = 23 Solving -1 + h = 23 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + h = 23 + 1 Combine like terms: -1 + 1 = 0 0 + h = 23 + 1 h = 23 + 1 Combine like terms: 23 + 1 = 24 h = 24 Simplifying h = 24
| 11a-10a-20=19 | | 3(4-8k)-1=-61 | | 40q^2-40q-30=0 | | 1/4h-8= | | 37+x=-2(1-7x) | | 3x+7y=176 | | -4k-44k=36 | | .05x+15=y | | (a-7)(2a+9)= | | 1u^2-4u-45=0 | | 2x^2+102=-60 | | 3X+4=22whatisX | | 10r=90 | | U^2-4u-45=0 | | -8(-2+2x)+8=-40 | | 72=4y+12 | | f(x)=-0.0009x^2+0.2088x | | 6h+13=5 | | m+123+29=180 | | -3-(-56)= | | -d^2+d=-6 | | f=3(22) | | -2+2.3w=10 | | 4(a+3)=6a+12 | | m+123+23=180 | | 12x+11+-4= | | 266=-7(-7x+11) | | x+15=7x-9 | | 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 |